Autoantibody detection to tumor-associated antigens of P53, IMP1, P16, cyclin B1, P62, C-myc, Survivn, and Koc for the screening of high-risk subjects and early detection of esophageal squamous cell carcinoma - Zhou, S. L.; Yue, W. B.; Fan, Z. M.; Du, F.; Liu, B. C.; Li, B.; Han, X. N.; Ku, J. W.; Zhao, X. K.; Zhang, P.; Cui, J.; Zhou, F. Y.; et al. (Diseases of the esophagus, 2014)
Summary The aim of this study was to evaluate the diagnostic values by detecting sera autoantibodies to eight tumor‐associated antigens (TAAs) of P53, IMP1, P16, cyclin B1, P62, C‐myc, Survivn and Koc full‐length recombinant proteins for the screening of high‐risk subjects and early detection of esophageal squamous cell carcinoma (ESCC). Enzyme‐linked immunosorbent assay was used to detect autoantibodies against the eight selected TAAs in 567 sera samples from four groups, including 200 individuals with normal esophageal epithelia (NOR), 214 patients with esophageal basal cell hyperplasia (BCH), 65 patients with esophageal dysplasia (DYS), and 88 patients with ESCC. In addition, the expression of the eight antigens in esophageal tissues was analyzed by immunohistochemistry. Statistically significant distribution differences were identified among the four groups for each of the individual autoantibodies to six TAAs (P53, IMP1, P16, cyclin B1, P62, and C‐myc); the detection rates of antoantibodies were positively correlated with the progression of ESCC. When autoantibody assay successively accumulated to six TAAs (P53, IMP1, P16, cyclin B1, P62, and C‐myc), a stepwise increased detection frequency of autoantibodies was found in the four sera groups (6% in NOR, 18% in BCH, 38% in DYS, and 64% in ESCC, respectively), the risks to BHC, DYS, and ESCC steadily increased about 3‐, 9‐, and 27‐folds. The sensitivity and the specificity for autoantibodies against the six TAAs in diagnosing ESCC reached up to 64% and 94%, respectively. The area under the receiver operating characteristic curve for the six anti‐TAA autoantibodies was 0.78 (95% confidence interval 0.74–0.83). No more increasing in sensitivity was found with the addition of new anti‐TAA autoantibodies. A combination detection of autoantibodies to TAAs might distinguish ESCC patients from normal individuals and the patients with esophageal precancerous lesions.